1969
DOI: 10.1021/jo01255a017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of derivatives of 2,3-diamino-2,3-dideoxy-D-galactose

Abstract: The rearrangement which took place in the preparation of 2 is known."6The dibromide 2, on treatment with triethyl phosphite, gave the phosphonate 3 in 70% yield based on the Czcr diol. Selective reduction of 3 with Lindlar catalyst' resulted in retinyl phosphonate (4). The nmr spectra and the analytical data of 2 4 were compatible with the assigned structures.The phosphonate 4 and vitamin A aldehyde 5 were stirred with sodium methoxide in pyridine at 0 ' to yield 0-carotene. The reduction of an ethynyl functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1969
1969
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…On dissolving D-mannitol and bromoacetaldehyde diethyl acetal (BEA) in [3][4][5][6][7][8][9][10][11][12] N hydrochloric (or sulfuric) acid, exploratory investigations established that a mono-O-bromoethylidene-D-mannitol formed rapidly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On dissolving D-mannitol and bromoacetaldehyde diethyl acetal (BEA) in [3][4][5][6][7][8][9][10][11][12] N hydrochloric (or sulfuric) acid, exploratory investigations established that a mono-O-bromoethylidene-D-mannitol formed rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…The esters differed strongly in their rotations and melting points, and the ester arising from the yellow isomer formed yellow crystals, too, whereas the other ester was colorless like its acid. It will be shown that the colorless acid was methyl 4,6-O-benzylidene-2-(2-carboxyanilino)-2,3-dideoxy-3-nitro-|3-D-glucopyranoside (2) and that the yellow acid was methyl 4,6-0-benzylidene-2-(2-carboxyanilino)-2,3-dideoxy-3-nitro-0-D-mannopyranoside (9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation